2011
DOI: 10.1111/j.1365-2702.2011.03815.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of leadership style in hospitals: a grounded theory study

Abstract: Managers of the hospitals demonstrate power and misuse obedience through their leadership style, resulting in deterioration of nurses' work environment. Nurses' managers are not given enough power by the hospitals in Taiwan. Subsequently, nurses feel themselves the lowest and most powerless subordinates. This study reveals that the Chinese cultural burdens are embedded in the leadership of Taiwanese hospitals. These findings enhance the knowledge of leadership and add to the understanding of managerial attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
(32 reference statements)
0
22
1
Order By: Relevance
“…There was a void in their discussion about influence at a more structural/organizational level. In that, our findings differ from other international studies, for example, in Taiwan, Su et al (2012) raise structural issues of overcoming hierarchical authority to enhance nursing leadership, in Fiji, Stewart and Usher (2010) raise concerns about the impact on patient safety and outcomes when nursing does not have a place in the hierarchy that allows a full contribution, in Jordan, Mrayyan and Khasawneh (2008) call for innovative and transformational nursing leaders using supportive behaviours to develop health-care delivery and, in Australia, Halcomb et al (2008) identify the need for a leadership culture that aims to improve health outcomes for patients. It is possible that the differences between studies are explained by the cultural individuality of the diverse studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…There was a void in their discussion about influence at a more structural/organizational level. In that, our findings differ from other international studies, for example, in Taiwan, Su et al (2012) raise structural issues of overcoming hierarchical authority to enhance nursing leadership, in Fiji, Stewart and Usher (2010) raise concerns about the impact on patient safety and outcomes when nursing does not have a place in the hierarchy that allows a full contribution, in Jordan, Mrayyan and Khasawneh (2008) call for innovative and transformational nursing leaders using supportive behaviours to develop health-care delivery and, in Australia, Halcomb et al (2008) identify the need for a leadership culture that aims to improve health outcomes for patients. It is possible that the differences between studies are explained by the cultural individuality of the diverse studies.…”
Section: Discussioncontrasting
confidence: 99%
“…, Su et al . ) with foci upon different health‐care contexts with requisite cultural dimensions. Common areas of international interest can be identified such as nursing staff absence (Davey et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that nurses have difficulty using power and in becoming powerful professionals (Su et al . ). Although research findings in Turkey and several other countries have indicated that nurses see themselves as powerless, there is no research on how nurses assess themselves in terms of possessing both personal and positional powers.…”
Section: Introductionmentioning
confidence: 97%
“…Theoretically, errors promote constructive changes in clinical practice when nurses are encouraged to use adaptive error-coping strategies within a supportive, nonblaming culture. 29 The difference in the social ranking between physicians and nurses and the enculturated managerial tendencies of using power and requiring obedience might be major obstacles to framing a teamwork structure. 27 Therefore, they tend to be silent and reluctant to express their safety concerns as they face pressure from physicians or higher ranked nurses.…”
Section: Discussionmentioning
confidence: 99%